2008
DOI: 10.1038/npp.2008.101
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Tractography in Mesencephalic Bundles: Relation to Mental Flexibility in Detoxified Alcohol-Dependent Subjects

Abstract: Components of the corticocerebellar circuit and the midbrain individually play a central role in addictive processes and have been associated with altered volumes and impairment of cognitive flexibility in alcohol-dependent subjects. The microstructure of white matter bundles composing the corticocerebellar network and passing through the midbrain was studied using diffusion tensor imaging in a group of detoxified alcohol-dependent men (n ¼ 20) and a group of healthy men (n ¼ 24). The relationship between prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 58 publications
2
57
2
1
Order By: Relevance
“…Specifically, alcoholics show an anterior-posterior gradient of commissural abnormalities (Pfefferbaum, Rosenbloom, Adalsteinsson, & Sullivan, 2007;Pfefferbaum, Rosenbloom, Fama, Sassoon, & Sullivan, 2010) and a superior-inferior gradient of association and projection fiber systems abnormalities (Pfefferbaum, Rosenbloom, Rohlfing, & Sullivan, 2009). DTI studies have also identified functional correlates and even double dissociations indicating selectivity between fiber system and function (e.g., Chanraud et al, 2009;Pfefferbaum et al, 2006Pfefferbaum et al, , 2009. For example, greater diffusivity in the genu was selectively predictive of working-memory performance, whereas greater diffusivity in the splenium was selectively predictive of performance on a spatial-reasoning task .…”
Section: Brain Macrostructure: Quantitative Dtimentioning
confidence: 94%
See 3 more Smart Citations
“…Specifically, alcoholics show an anterior-posterior gradient of commissural abnormalities (Pfefferbaum, Rosenbloom, Adalsteinsson, & Sullivan, 2007;Pfefferbaum, Rosenbloom, Fama, Sassoon, & Sullivan, 2010) and a superior-inferior gradient of association and projection fiber systems abnormalities (Pfefferbaum, Rosenbloom, Rohlfing, & Sullivan, 2009). DTI studies have also identified functional correlates and even double dissociations indicating selectivity between fiber system and function (e.g., Chanraud et al, 2009;Pfefferbaum et al, 2006Pfefferbaum et al, , 2009. For example, greater diffusivity in the genu was selectively predictive of working-memory performance, whereas greater diffusivity in the splenium was selectively predictive of performance on a spatial-reasoning task .…”
Section: Brain Macrostructure: Quantitative Dtimentioning
confidence: 94%
“…Rather, chronically alcohol-dependent men and women without obvious complications from nutritional deficiencies or hepatic disorders demonstrate in vivo visually detectable cortical and cerebellar shrinkage relative to the controls (Hayakawa & Kumagai, 1992;Shear, Jernigan, & Butters, 1994;Wang et al, 1993). Specific regions and tissue affected by chronic alcohol exposure and quantified volumetrically include cortical gray and white matter (Cardenas, Studholme, Meyerhoff, Song, & Weiner, 2005;Jernigan et al, 1991;Pfefferbaum et al, 1992), particularly prefrontal areas in older alcoholics (Cardenas, Studholme, Gazdzinski, Durazzo, & Meyerhoff, 2007;Pfefferbaum, Sullivan, Mathalon, & Lim, 1997), mammillary bodies (Shear, Sullivan, Lane, & Pfefferbaum, 1996;Sullivan et al, 1999), hippocampus (Agartz, Momenan, Rawlings, Kerich, & Hommer, 1999;Beresford et al, 2006;Sullivan, Marsh, Mathalon, Lim, & Pfefferbaum, 1995), amygdala (Makris et al, 2008), thalamus (Chanraud et al, 2007;De Bellis et al, 2005;Sullivan, 2003), caudate nucleus and putamen (Sullivan, Deshmukh, De Rosa, Rosenbloom, & Pfefferbaum, 2005), pons (Chanraud et al, 2009;Pfefferbaum, Rosenbloom, Serventi, & Sullivan, 2002;, parietal cortex (Fein, Shimotsu, Chu, & Barakos, 2009), and cerebellum (De Bellis et al, 2005;Sullivan, Deshmukh, Desmond, Lim, & Pfefferbaum, 2000). Longterm abstinent alcoholics with psychiatric comorbidities show more enduring subcortical volume deficits than those free of such psychopathology (Sameti, Smith, Patenaude, & Fein, 2011).…”
Section: Brain Macrostructure: Quantitative Mrimentioning
confidence: 96%
See 2 more Smart Citations
“…Many previous DTI studies associates the reduction of FA in the genu of the corpus callosum, centrum semiovale (32) and areas in the frontal and superior sites such as frontal forceps, internal and external capsules, and fornix (33) which suggests a demyelination of fiber tract and axonal degeneration (34). Another DTI studies reveal that white matter fibers from midbrain and pons are disrupted by chronic alcohol intake affecting cognitive abilities (35) and abnormalities in motivational and reward related brain areas (36). Alcohol does not affect males and females in the same way.…”
Section: Brain Imaging To Identify Neuroanatomical Basis Of Alcohol Amentioning
confidence: 99%